(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
Background: Bronchial asthma can cause many morbidities such as heart disease, diabetes mellitus, and hypertension, but the impact of asthma on renal function is not yet verified. This study aims to clarify the association between bronchial asthma and the risk of developing renal dysfunction. Methods: The study was conducted in Merjan Medical City in the period from November 2014 to May 2015, it included 75 patients with acute exacerbation of asthma and 70 control healthy subjects who completed medical questionnaires, pulmonary function tests, measurement of blood urea and serum creatinine, in addition to measurement of oxygen saturation (SPO2) by oximeter. Hypoxic patient has level of SPO2 less than 95%. Statistical analysis was done, P values ≤0.05 were considered to be clinically significant. Results: There was no significant difference in mean age and gender between both groups. There was significant difference in the mean values of blood urea (Bur) and serum creatinine (Scr) before and after treatment for all patients, Bur increased and Scr decreased significantly in hypoxic group in comparison with non-hypoxic group (P ˂ 0.05). In addition, the study showed a significant correlation between blood urea and SPO2 (before treatment) (p < 0.05), while non-significant negative correlation between serum creatinine and SPO2 (before treatment) (r = 0.1, P > 0.05). The results revealed that the Bur and Scr increased significantly in male group in comparison to female group (P˂0.05). Also there was no significant correlation between blood urea and serum creatinine with forced expiratory volume in first second (FEV1) (before treatment) (P > 0.05). Conclusions: The study showed high percentage of asthmatic patients admitting in the hospital wards had abnormalities of renal function tests at the first days of admission to hospital, but most patients return to normal state gradually after getting treatment. The mechanisms and clinical implications of kidney dysfunction in patients with asthma need further investigation in addition to follow up for those patients to determine who of them will get chronic renal failure at future.